Pemodelan Statistik Pemberian Air Susu Ibu (ASI) Eksklusif Berdasarkan Faktor Demograli - SARAH ZAIDAN; SWASONO R. TAMAT; NURITA ANDAYANI; ANNY VICTOR PURBA (JURNAL ILMU KEFARMASIAN INDONESIA, 2012)
Exclusive breastfeeding is defined as giving breast milk to a baby without any additional drink, food or beverages during the first 6 months after birth. Today there is a decline in exclusive breastfeeding, and among others, one reason is the increase in the participation of mothers in the workforce, especially in urban areas. Many factors that affect the regularity of exclusive breastfeeding by working mothers, one of which, is the demographic factor. This study aims to obtain profile data of exclusive breastfeeding by working mothers and statistical modelling of exclusive breastfeeding by working mothers based on demographic factor, by conducting a survey on 384 respondents. This research uses descriptive analysis and logistic regression analysis with SPSS software version 15.0. Descriptive analysis showed that most mothers working in Jakarta (61.2%) did not give exclusive breastfeeding. Logistic regression statistical analysis showed that age, occupation, distance to work, and travel time to the workplace of working mothers are dominant factors that influence exclusive breastfeedings, with the p-value is smaller than the p value (Sig) = 0.05.